COMPARATIVE ANALYSIS OF FINANCING MODELS OF HIGHER EDUCATION - Pranevičienė, Birutė; Pūraitė, Aurelija; Vasiliauskienė, Violeta; Simanavičienė, Žaneta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper aims to present a comparative analysis of financing models of higher education in Europe. Higher education institutions can function properly and ensure the quality of research and studies when there is sufficient funding. Higher education institutions in Europe face a demanding financial situation in which traditional models of funding have been transformed and continue to change gradually. The paper consists of two parts. In the first part the trends in financing higher education in Europe are presented and evaluated. An analysis of the legal regulation and deficiencies of this field are presented. The second part of the paper is devoted to the description of state financing methods of higher education. The main methods of the distribution of the state financing among the institutions of higher education are discussed and the advantages and disadvantages of those methods are evaluated, as well as the experience of other countries in financing higher education. The problematic aspects of the state regulation of financing higher education are analysed by using the methods of document analysis, critical-analytical methods, analysis of scientific literature, historic analysis, systematic analysis, method of the source-content analysis, comparative method.